IMHA Music Enterprise / Helvisius Jesus Pele ... [et al.] - Jesus Pele, Helvisius; Ibrahim, Azlan; Josef, Ivan Armand; Anwar, Mhd Maswan (2009)
'IMHA Music Enterprise' is the name of our business. We choose this name because IMHA represented of our name which is I stand for Ivan Armand Jozef, M for Mhd. Maswan Bin Anwar, H for Helvisius Jesus Pele and A for Azlan Bin Ibrahim. Moreover, this name is familiar and easier to remember by the customer and will attract them to come again. The concept of this business is to buy instruments. We are not only selling instrument but also provide teaching service. We choose this business because it had a very big potential of profit. As we know, nowadays people like to explore their talent because there are many reality programs that influence them. Furthermore, students can also release their tension. Our business also can help the government to reduce social problem because people can fulfill their leisure time goodly.